INVENTARISASI SERANGGA AIR DI DESA BUNGURCOPONG KECAMATAN PICUNG PANDEGLANG BANTEN - Meliawati Meliawati; Suyamto Suyamto; Nurullah Asep Abdillah; Mujijah Mujijah; Usman Setiawan (Bioscientiae, 2024)
Water insects are a group of insect organisms that partially or phase of their life  in water. Usually the habitat of the nymph phase in the imago phase, that is the nymphs usually live in water. In naiads there are breathing apparatus such as gills and their habitat is in water While in the immago phase, the habitat is on land or air and the breathing apparatus uses the trachea. This study to determine the diversity of aquatic insects in the river Cimoyan Picung District. The search was carried out at 2 stations with 3 times taking itat each station. Sampling using a kick net with a plot of 10 meters at each station. Samples that can be preserved with formalin solution, the sorted, in the insectarium and identified. The data obtained from the research of aquatic insects in the village of Bungurcopong, Picung Pandeglang district used descriptive data.